2015
DOI: 10.3746/pnf.2015.20.4.253
|View full text |Cite
|
Sign up to set email alerts
|

High Hydrostatic Pressure Extract of Red Ginseng Attenuates Inflammation in Rats with High-fat Diet Induced Obesity

Abstract: Chronic low-grade inflammation is associated with obesity. This study investigated effect of high hydrostatic pressure extract of red ginseng (HRG) on inflammation in rats with high-fat (HF) diet induced obesity. Male, SpragueDawley rats (80∼110 g) were randomly divided into two groups, and fed a 45% HF diet (HF) and a 45% HF diet containing 1.5% HRG (HF+HRG) for 14 weeks. At the end of the experiment, the serum leptin level was reduced by the HRG supplementation. The mRNA expression of genes related to adipog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Our findings are supported by previous studies describing that red ginseng downregulates PPARγ and aP2 expression in adipose tissue of rats with HFD-induced obesity (Jung et al, 2015) and androgens such as testosterone and dihydrotestosterone downregulate PPARγ and C/EBPα expression in human adipose stem cells (Chazenbalk et al, 2013). These results support our hypothesis that decreased body weight gain, adipose tissue mass, and adipocyte size following GE and testo sterone treatments are due to the downregulation of adipogenesis genes.…”
Section: Discussionsupporting
confidence: 82%
“…Our findings are supported by previous studies describing that red ginseng downregulates PPARγ and aP2 expression in adipose tissue of rats with HFD-induced obesity (Jung et al, 2015) and androgens such as testosterone and dihydrotestosterone downregulate PPARγ and C/EBPα expression in human adipose stem cells (Chazenbalk et al, 2013). These results support our hypothesis that decreased body weight gain, adipose tissue mass, and adipocyte size following GE and testo sterone treatments are due to the downregulation of adipogenesis genes.…”
Section: Discussionsupporting
confidence: 82%
“…We observed that HT048 supplementation suppresses pro-inflammatory cytokines, MCP-1, and TNF-α. MCP-1 and TNF-α contribute to monocyte recruitment intro WAT and pathogenesis of obesity-linked complications in WAT, respectively [46]. Our results suggest that decreased WAT mass in HT048 groups is strongly associated with downregulation of adipogenesis genes and pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 75%
“…WAT is composed primarily of mature adipocytes, which are generated through the proliferation of preadipocytes [45]. Chronic inflammation is a characteristic of obesity that is caused because mature adipocytes inducing expression of pro-inflammatory cytokines genes including MCP-1 and TNF-α [46]. We observed that HT048 supplementation suppresses pro-inflammatory cytokines, MCP-1, and TNF-α.…”
Section: Discussionmentioning
confidence: 90%
“…The dosages of the extracts used in this study were based on those used in previous studies on the efficacy of chronic intake of dietary ginseng extract on obesity in rats. In these studies, no effect was observed with the use of RG at 2,000 mg/kg/d [21] , [22] . All the experimental procedures used were approved by the Institutional Animal Care and Use Committee of Chungnam National University (CNU-00245; Daejeon, Korea).…”
Section: Methodsmentioning
confidence: 77%